Translation of Movie Titles from English into Persian: Strategies and Effects - Lotfollahi, Bahareh; Moinzadeh, Ahmad (Mediterranean Journal of Social Sciences, 2012)
Movies are one of the most popular and influential mass media in the world. Movie titles are the inseparable parts of themovies. Translation of movie titles is a demanding job which needs much effort. Iran has long been a market for western movies whichare rapidly being translated from English into persian. It seems that translation of movie titles from English into persian has not receivedmuch attention. Therefore, the present study made an attempt to investigate the translation of Hollywood movie titles of 2010 fromEnglish into Persian in order to analyze the kind of translation strategies and procedures which were used and to show how thesestrategies changed the effect each title creates. It was shown that the most frequently used translation strategies were literal translationand transliteration which could change the effect of the main titles.